The Use of Quizziz to Improve Students’ Reading Skill - Tarina Dashela; Yeni Mustika (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This research aims to describe the improvement of the students’ reading skill by using Quizziz. It was conducted on Classroom Action Research in two cycles. The participants were second-semester students in Bina Sarana Informatika University Pontianak which consisted 30 students. The steps of Classroom Action Research were planning, acting, observing, and reflecting. The data collection was done by the researcher which are observation checklist, interview, and individual test. The findings of this research showed that the students were motivated and actively participated in the online class. The atmosphere will be more fun and interesting. When the students learn in a fun way, their comprehension will be easier to get. This is an effective way to learn English and to improve students’ reading skills.